OC-081 Nutritional Optimisation of Pre-Surgical Crohn's Disease Patients with Enteral Nutrition Significantly Decreases Length of Stay and Need for a Stoma. (17th August 2016) - Patel, KV; Sandall, AM; O'Hanlon, DV; Darakhshan, AA; Williams, AB; Westcott, E; Irving, PM; Lomer, MC; Sanderson, JD
Abstract : Introduction: There is a lack of evidence for a clear nutritional optimisation strategy of pre-surgical Crohn's disease (CD) patients. Limited data suggests that pre-surgical enteral nutrition (EN) increases albumin and decreases CRP as well as reducing anastomotic leakage, intra-abdominal abscess formation and wound infection. We aimed to assess the effect of nutritional optimisation of pre-surgical CD patients with EN on peri- and post-surgical outcomes and anthropometrics. Methods: CD patients (n = 32) requiring ileal or ileocolonic resection were identified and nutritionally optimised pre-surgery using a minimum of 6 weeks EN (Modulen IBD, Nestle, Vevey, Switzerland) providing 75–100% nutritional requirements. Peri-surgical (albumin and CRP) and post-surgical (total length of stay, complication rate, readmission days and stoma formation) outcomes were compared with a retrospective sample of control patients (n = 35) who had not been nutritionally optimised. A subset of nutritionally optimised patients underwent anthropometric analysis pre and post EN. Continuous data are presented as mean ± sd and paired and independent t-tests were used for comparison where appropriate. Categorical data were compared using Chi squared tests. p < 0.05 was considered significant. Results: Nutritionally optimised patients had significantly shorter total length of stay compared with control patients (9.81 ± 9.97 d vs 16.34 ± 9.95 d, p = 0.009). Only 6 (19%) nutritionally optimised patients versus 19 (54%) control patients had stoma formation (p = 0.005). Nutritionally optimised patients had significantly fewer complication-related readmission days than control patients (0.69 ± 0.37 d vs 1.75 ± 3.64 d, p = 0.02). Twenty six (81%) nutritionally optimised patient had a normal albumin level pre-surgery versus 21 (60%) control patients (p = 0.002) and 20 (63%) nutritionally optimised patients had normal pre-surgery CRP versus 11 (31%) control patients (p = 0.001). Eleven patients (35.3 ± 13.3 years, 5 males) were included in the nutritionally optimised subset analysis. BMI did not change from pre to post EN (23.58 ± 5.04 kg/m2 to 23.03 ± 3.77 kg/m2; p = 0.336) nor did mid arm muscle circumference, waist circumference and handgrip strength. Conclusion: Optimisation of nutrition pre-surgery in CD appears to reduce length of stay, stoma rate and additional hospital in-patient days for complications as well as improving albumin and CRP. However it is unclear what anthropometric measurements are useful to assess the effects of EN on nutritional status. Disclosure of Interest: None Declared